Knowledge, attitudes and uptake related to influenza vaccine among healthcare workers during the 2018-2019 influenza season in Tunisia - Ines Cherif; Ghassen Kharroubi; Leila Bouabid; Adel Gharbi; Aicha Boukthir; Nissaf Ben Alaya; Afif Ben Salah; Jihene Bettaieb (BMC, 2021)
Abstract Background The influenza vaccine (IV) is considered the most effective strategy to prevent seasonal influenza infection and annual vaccination of healthcare workers (HCWs) is recommended by the World Health Organization given their high mixing with patients. We assessed IV uptake among HCWs in the 2018-2019 season and explored their knowledge and attitudes regarding influenza immunization. Methods A cross-sectional study was conducted in 150 representative Tunisian health facilities from March to May 2019. We recruited 1231 HCWs with direct patient contact using self-weighted multistage sampling. Univariate and multivariate logistic regression analyses permitted to assess the factors associated with IV uptake in the 2018-2019 influenza season. Results Among 1231 health professionals enrolled in this study, less than half (36.6, 95% confidence interval [CI]: 33.9-39.4) received the IV at least once in their lives and only 15.3% (CI: 13.3-17.4) were vaccinated against influenza in the 2018-2019 influenza season. High confidence regarding IV efficacy, belief about the mandatory character of influenza vaccination for HCWs, and IV uptake in the 4 years preceding the 2018-2019 influenza season were independently associated with higher IV uptake by multivariate analysis. However, participants with high educational level were less likely to receive the IV than those with the lowest educational level. Conclusions Our study revealed a low vaccination rate among Tunisian HCWs confirming the importance of tailored education programs targeting this population.